2021
DOI: 10.3389/fpsyg.2021.733896
|View full text |Cite
|
Sign up to set email alerts
|

Shared Representations in Athletes: Segmenting Action Sequences From Taekwondo Reveals Implicit Agreement

Abstract: How do athletes represent actions from their sport? How are these representations structured and which knowledge is shared among experts in the same discipline? To address these questions, the event segmentation task was used. Experts in Taekwondo and novices indicated how they would subjectively split videos of Taekwondo form sequences into meaningful units. In previous research, this procedure was shown to unveil the structure of internal action representations and to be affected by sensorimotor knowledge. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…When observing movements, it has been shown that event boundaries relate to salient kinematic features (Zacks et al, 2009;Newberry et al, 2021). Event segmentation even works for movements characterized by rapid kinematic changes like tasks in gymnastics (Bläsing, 2015;Newberry et al, 2021;Stadler et al, 2021), in contrast to eye-tracking where short fixations of the eyes with a rapidly changing visual scene is difficult to track (Mack, 2020). Therefore, and according to the theoretical grounding about the relevance of kinematic features for decision making in gymnastics, event segmentation was used in the current study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When observing movements, it has been shown that event boundaries relate to salient kinematic features (Zacks et al, 2009;Newberry et al, 2021). Event segmentation even works for movements characterized by rapid kinematic changes like tasks in gymnastics (Bläsing, 2015;Newberry et al, 2021;Stadler et al, 2021), in contrast to eye-tracking where short fixations of the eyes with a rapidly changing visual scene is difficult to track (Mack, 2020). Therefore, and according to the theoretical grounding about the relevance of kinematic features for decision making in gymnastics, event segmentation was used in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, a disadvantage of test outcomes as reference is that for many tasks in PE no tests exist. An alternative approach, therefore, is to utilize trainers who hold a sufficient level of judgment accuracy with regard to the studied task as reference (Bläsing, 2015;Mack, 2020;Newberry et al, 2021;Stadler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The cognitive structuring of exercises in terms of movement phases and characteristics can be assessed using event segmentation (Kurby & Zacks, 2008;Zacks & Swallow, 2007). In research related to sport science, event segmentation has so far been repeatedly applied in studies focussing on cognitive aspects of movement expertise (Bläsing, 2015;Newberry et al, 2021;Stadler et al, 2021). Event segmentation is generally concerned with the idea of how people automatically compartmentalise experience into temporally defined units.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, a disadvantage of test outcomes as reference is that for many exercises in physical education, no tests exist. An alternative approach, therefore, is to utilise trainers who hold a sufficiently high level of judgment accuracy with regard to the studied exercise as reference (Bläsing, 2015;Mack, 2020;Newberry et al, 2021;Stadler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%